STRATEGI HUMAS DALAM MEMBANGUN CITRA POSITIF MELALUI KOMUNIKASI TERBUKA DAN OPTIMALISASI MEDIA DIGITAL DI SEKOLAH DASAR ISLAM TERPADU NURUL ‘ILMI 2 KOTA JAMBI - Marcella Novia Putri; Muhammad Syifaa'ul Qolbi; Akhmad Habibi; Friscilla Wulan Tersta (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze public relations (PR) strategies in building a positive school image through the implementation of open communication and the use of digital media at SDIT Nurul 'Ilmi 2, Jambi City. This institution emphasizes flagship programs such as Quran memorization and tajweed, bilingual instruction, leadership development, and the development of noble character. Despite facing public perceptions of the relatively high cost of integrated Islamic education, this Islamic elementary school needs to clearly and persuasively convey the essence, quality, and superiority of its services to the public. The study used a qualitative approach with a case study design. Data collection was conducted through in-depth interviews, observation, and documentation, while data analysis used the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results show that public relations strategies based on open communication and digital media optimization contribute to increasing public trust and strengthening the school's image. Supporting factors include the support of school leaders, the competence of human resources in public relations, and parental participation. Inhibiting factors include limited time and technical skills in managing digital media.